Betacyanin and Growth of Beetroot (Beta vulgaris L.) in Response to Nitrogen Fertilization in a Tropical Condition - S. M. Sitompul; Ajrina Puspita Zulfati (AGRIVITA, Journal of Agricultural Science, 2019)
A series of studies was carried out to explore the possibility of beetroot cultivation in the tropics on highlands.  This was initiated by a study on the effect of temperature and duration of beetroot storage on betacyanin content after determination of a wavelength giving the maximum absorbance of betacyanin extracts from beetroots.  The second study was designed to examine the response of betacyanin and plant growth to nitrogen (N) fertilization.  A randomized block design was used to impose the treatment of N fertilizer (Urea) consisting of 0, 0.15, 0.30, 0.45, and 0.60 g N per plant with five replicates.  The maximum absorbance of betacyanin extracts from fresh beetroots was attained at the wavelength of 536 nm.  Betacyanin content of beetroots increased with duration of storage up to 7 days from 229 ml l-1 to 639 ml l-1 when stored at room temperature (± 220C), and was reduced after slight increases when stored at lower temperatures.  Nitrogen fertilization reduced betacyanin content of beetroots with a reduction of up to 25%, from 351.5 to 257.6 ml l-1, with the application of 0.6 g N plant-1.  Root yield and total dry weight (TDW) increased with the supply of N fertilizer.